Mirror symmetry and conformal flatness in general Relativity - P. Gravel; C. Gauthier (International Journal of Mathematics and Mathematical Sciences)
Using symmetry arguments only, we show that every spacetime with mirror-symmetric spatial sections is necessarily conformally flat. The general form of the Ricci tensor of such spacetimes is also determined.